Probability Space of Stochastic Fractals - Virchenko, Yu. P.; Shpilinskaya, O. L. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We develop a general method for the construction of a probability structure on the space F of random sets in ℝ. For this purpose, by using the introduced notion of c-system, we prove a theorem on the unique extension of a finite measure from a c-system to the minimal c-algebra. The obtained structure of measurability enables one to determine probability distributions of the c-algebra of random events sufficient, e.g., for the so-called fractal dimensionality of random realizations to be considered as a measurable functional on F.